Porous SiO composite tailored by scalable mechanochemical oxidation of Si for Li-ion anodes. (10th October 2020) - Park, Dahye; Kim, Han-Seul; Seo, Hyungeun; Kim, Kyungbae; Kim, Jae-Hun
Highlights: The porous SiO composite was prepared by mechanochemically oxidizing Si powder. Micro- and nano-sized Si powders were used as a starting material. Si nanocrystallites were embedded in an amorphous silicon suboxide matrix. The microstructure modification led to improved electrochemical properties. Abstract: In this study, we propose a simple strategy for the mass-production of a porous SiO material as an anode material for rechargeable Li-ion batteries. The porous SiO composite was prepared by mechanochemically oxidizing inexpensive Si powder while simultaneously reducing ZnO powder using a high-energy ball milling process. The resulting Zn of the SiO/Zn composite was chemically removed by acid-aided etching. Both micro- and nano-sized Si powders were used as a starting material to compare their final microstructure and electrochemical properties. X-ray diffraction and X-ray photoelectron spectroscopy were employed to confirm the mechanochemical synthesis of the SiO materials. Electron microscopy analyses with elemental mapping demonstrated that the SiO composite had a Si nanocrystallite embedding microstructure in an amorphous silicon suboxide matrix with highly abundant inside mesopores. The porous SiO composite electrode exhibited improved electrochemical properties over a commercially available SiO electrode because of its microstructure modification. Also, the effects of the starting Si powder's particle size on the resulting microstructure and electrochemical properties were thoroughly investigated with the abovementioned material and electrochemical characterization tools. Graphical abstract: Image, graphical abstract